2015
DOI: 10.3923/rjsb.2015.46.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sewage Sludge Urban Application on Concentration of Fe, Mn and Some Nutrient Element in Parsley

Abstract: Sewage sludge application on agricultural land as an organic fertilizer the recycling of valuable components such as many plant nutrients. Sewage sludge is rich in macro and micronutrients. However, high concentrations of heavy metals in sludge may cause pollution of soil, groundwater and the human food chain because of toxic metal uptake by crops. The objective of this research was to investigate the effect of sewage sludge application on concentration of iron and manganese in parsley. This study were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…However, our results showed that the N application from mineral fertilizers can be partially replaced by SS and reach large yields (Macedo et al, 2012;Motta and Maggiore, 2013;Yagmur et al, 2017). Our study also showed that even with the large imbalance between the amount of micronutrients contained in SS and the amount required by maize plants, SS proved to be efficient in providing micronutrients to maize plants (Pigozzo et al, 2000;Macedo et al, 2014;Nikzad et al, 2015).…”
Section: Discussionsupporting
confidence: 51%
“…However, our results showed that the N application from mineral fertilizers can be partially replaced by SS and reach large yields (Macedo et al, 2012;Motta and Maggiore, 2013;Yagmur et al, 2017). Our study also showed that even with the large imbalance between the amount of micronutrients contained in SS and the amount required by maize plants, SS proved to be efficient in providing micronutrients to maize plants (Pigozzo et al, 2000;Macedo et al, 2014;Nikzad et al, 2015).…”
Section: Discussionsupporting
confidence: 51%